Studying Digital Pentecostalism: Empirical-Theological Hermeneutics, Ethnography, and the Internet - Cartledge, Mark J. (Pneuma, 2022)
One of the most important developments in recent history has been the invention of the internet and this has led to many academic disciplines developing digital research competence. However, there has been limited practical-theological research completed in the area of digitally mediated Pentecostalism. Therefore, this article addresses this important area, as conceived within the discipline of practical theology using empirical research methods. Even before the impact of the COVID-19 pandemic, many Pentecostals had embraced an online delivery of worship and ministry. Nevertheless, the capacity for the digital mediation of beliefs and practices has developed considerably in 2020 and 2021, and these recent developments invite further critical attention. To develop competence in the study of digital Pentecostalism, practical theologians will be required to acquire competence in “virtual ethnography,” sometimes referred to as “netnography,” that is, the academic study of online communities, including online churches. As part of this competence, there is a need to reframe virtual ethnography within an empirical-theological approach as a subset of practical theology, and this includes attending to hermeneutical issues as well as technical competence (that is, methods of gathering and evaluating online data). In this article, I shall explore some of these methodological concerns and suggest ways in which scholars can develop approaches to the research of digital pentecostal and charismatic Christianity.